Effects of Centrality of Religiosity and Dyadic Coping on Psychological Well-Being of Married Couples who Postpone Parenthood - Dorota Czyżowska; Alicja Kalus; Anna Wendołowska (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
Religiosity and dyadic coping are among the factors important for the quality of marriage, satisfaction with the relationship and the sense of happiness of the spouses. Well-being, mainly in the aspect of personal development or life goals, seems to be particularly important for couples planning to conceive a child in the near or distant future. The study involved 51 married couples postponing parenthood. Their dyadic coping, psychological well-being and the centrality of religiosity were studied. The actor-partner interdependence model was used for the dyadic analyses. There were no differences in the well-being between the spouses, however, women rated in dyadic coping and religiosity higher. The centrality of the spouses’ religiosity, and especially the congruence of their religious beliefs, seems to have a significant impact on their well-being. The obtained results seem to shed new light on the importance of dyadic coping by spouses and their religiosity for the well-being of each of them.